2011
DOI: 10.4028/www.scientific.net/amr.233-235.1040
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Dynamic Simulation of Circulating Cooling Water Biofouling

Abstract: To study the formation mechanism and the chemical component of biofouling, the biofouling formation was simulated by the dynamic simulation device of circulating cooling water under the constant condition of 30°C and 0.4 m/s. The slime-forming bacteria and Iron Bacteria were selected as the research subject. Adsorption theory of bacteria in the solid/liquid interface was analyzed by colloidal stability theory. The two kinds of bacteria on heat transfer and the relationship between the total number of bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Researches have showed that the corrosion rate of metal surface is depended on the relationship between metal oxide solubility and pH value [8]. In acid solution, Fe 3+ is a kind of cathode oxidation accelerator.…”
Section: Cooling Water Fouling Mechanism Analysis Associated With Watmentioning
confidence: 99%
See 1 more Smart Citation
“…Researches have showed that the corrosion rate of metal surface is depended on the relationship between metal oxide solubility and pH value [8]. In acid solution, Fe 3+ is a kind of cathode oxidation accelerator.…”
Section: Cooling Water Fouling Mechanism Analysis Associated With Watmentioning
confidence: 99%
“…After decades of exploration and research by scholars, many studies about cooling water fouling mechanism had been done [5][6][7], however, it was still difficult to understand. Generally, the influence factors of cooling water fouling could be summarized as follows: operation conditions [8][9][10], water quality With the technology development, more and more scholars concern on factors correlation analysis. Zhao and Chen [18] tried to relate a number of factors to fouling rate, and classified these factors into three categories: solution composition, operating parameters, and heat exchanger surface characteristics, then discussed each aspect from the crystallization viewpoint At present, the research about cooling water fouling mechanism is still inadequate and the relationship between water parameters and fouling resistance are not clear.…”
Section: Introductionmentioning
confidence: 99%